Prevalence of hyperuricemia in patients with type 2 diabetes mellitus in tertiary care centre - Nagarkoti, Sujata; Subedi, Bhusan Kumar; Malla, Rewati Raman; Subedi, Shova (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: The incidence and prevalence of diabetes mellitus type 2 (T2DM) is increasing throughout the world. Diabetes is responsible for 6.7 million deaths in 2021- 1 in every 5 second. Patients with T2DM tend to have higher serum uric acid levels than normal population. Uric acid is associated with the onset of diabetes-related health complications including inflammation, oxidative stress, vascular endothelial injury. This study has been carried out to see prevalence of hyperuricemia in T2DM in our population. Identifying risk factors for progression of diabetic complications are also equally important for its early addressing or delaying progression of diabetic complication.Method: A hospital based cross-sectional study was done in which sixty five patients with T2DM were included from May 2021 to May 2022 who were admitted in ward or visited in general medicine OPD of Bir Hospital after ethical approval from the institutional review committee. The patients fulfilling inclusion criteria underwent anthropometric measurement and laboratory investigations. The data were entered and analyzed using statistical software IBM-SPSS version 25.Result: The prevalence of hyperuricemia (>7mg/dl for male & > 6mg/dl for female) was found to be 15.38% in patients with T2DM.Conclusion: There was prevalence of hyperuricemia among diabetes cases in this study. This forms a basis for screening hyperuricemia among patients with T2DM. Further studies with larger number of patients with T2DM are needed to explore prevalence and the relationship of hyperuricemia to other clinical and laboratory parameters of T2DM.